2021
DOI: 10.1111/ppl.13380
|View full text |Cite
|
Sign up to set email alerts
|

Emerging warriors against salinity in plants: Nitric oxide and hydrogen sulphide

Abstract: The agriculture sector is vulnerable to various environmental stresses, which significantly affect plant growth, performance, and development. Abiotic stresses, such as salinity and drought, cause severe losses in crop productivity worldwide. Soil salinity is a major stress suppressing plant development through osmotic stress accompanied by ion toxicity, nutritional imbalance, and oxidative stress. Various defense mechanisms like osmolytes accumulations, activation of stress‐induced genes, and transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 155 publications
0
31
0
Order By: Relevance
“…Applied NO has been found to counteract the detrimental effects of osmotic stressors, i.e., drought [ 13 ] and salinity [ 85 , 86 ]. These effects may be due to enhancing the antioxidant capacity, osmotic potential, nutrient homeostasis, and gas exchange [ 13 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Applied NO has been found to counteract the detrimental effects of osmotic stressors, i.e., drought [ 13 ] and salinity [ 85 , 86 ]. These effects may be due to enhancing the antioxidant capacity, osmotic potential, nutrient homeostasis, and gas exchange [ 13 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that salinity stress induces endogenous production of H 2 S in crop plants, which in turn enhances salinity tolerance by modulating the activity of antioxidant enzymes, increasing the osmolyte content, regulating cell signaling proteins, maintaining ionic homeostasis as well as regulating the expression of stress-linked genes (Shi et al, 2013;Zulfiqar & Hancock, 2020). Shi et al (2013) have reported a 2-to 4-fold increase in endogenous H 2 S production compared to control in response to salinity stress in Cynodon dactylon Evelin et al, 2019;Goyal et al, 2019Goyal et al, , 2021Hasanuzzaman et al, 2014;. Also, the impairment of biological processes, such as photosynthesis, nutrient uptake, and nutrient assimilation, was reported (Farooq et al, 2015).…”
Section: Effect Of Salinity On Endogenous H 2 S Productionmentioning
confidence: 99%
“…Due to these immensely beneficial features, the contribution of H 2 S has also been observed in the mitigation of salinity‐induced adverse effects on plant growth and development, particularly in photosynthesis, oxidative stress, and productivity (Dar et al, 2021). Further, during salinity stress alleviation, the contribution of other signaling components such as H 2 O 2 (Liu et al, 2020), NO (Goyal et al, 2021; Jahan et al, 2020), and melatonin (Li et al, 2019) was also reported, suggesting the possibility of their crosstalk. During the H 2 S‐mediated amelioration of salinity stress, H 2 S interacts either upstream or downstream to these signaling components.…”
Section: Introductionmentioning
confidence: 99%
“…However, research into its role in higher plant physiology has been increasing to a significant extent particularly over the last ten years. H 2 S is now reported to be involved in virtually all physiological processes, including seed germination, root development, senescence, fruit ripening and guard cell movements [5][6][7][8], and also in mechanisms of response to adverse environmental conditions, as well as to biotic and abiotic stresses [9][10][11][12][13][14][15][16][17][18][19]. Figure 1 shows a graphical summary of the key plant processes involving H 2 S. All these wide spectra of functions exerted by H 2 S are done usually in coordination with other molecules with regulatory properties such as nitric oxide, hydrogen peroxide, carbon monoxide, melatonin, abscisic acid, gibberellins, cytokinins, or ethylene.…”
Section: H 2 S Metabolism In Higher Plants: a Perspectivementioning
confidence: 99%
“…However, research into its role in higher plant physiology has been increasing to a significant extent particularly over the last ten years. H 2 S is now reported to be involved in virtually all physiological processes, including seed germination, root development, senescence, fruit ripening and guard cell movements [ 5 , 6 , 7 , 8 ], and also in mechanisms of response to adverse environmental conditions, as well as to biotic and abiotic stresses [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Figure 1 shows a graphical summary of the key plant processes involving H 2 S.…”
Section: H 2 S Metabolism In Higher Plants: a Perspectivementioning
confidence: 99%